Thriving not just surviving: A review of research on teacher resilience - Beltman, Susan; Mansfield, C.; Price, A. (Elsevier, 2011)
Retaining teachers in the early stages of the profession is a major issue of concern in many countries. Teacher resilience is a relatively recent area of investigation which provides a way of understanding what enables teachers to persist in the face of challenges and offers a complementary perspective to studies of stress, burnout and attrition. We have known for many years that teaching can be stressful, particularly for new teachers, but little appears to have changed. This paper reviews recent empirical studies related to the resilience of early career teachers. Resilience is shown to be the outcome of a dynamic relationship between individual risk and protective factors. Individual attributes such as altruistic motives and high self-efficacy are key individual protective factors. Contextual challenges or risk factors and contextual supports or protective factors can come from sources such as school administration, colleagues, and pupils. Challenges for the future are to refine conceptualisations of teacher resilience and to develop and examine interventions in multiple contexts. There are many opportunities for those who prepare, employ and work with prospective and new teachers to reduce risk factors and enhance protective factors and so enable new teachers to thrive, not just survive.